SYNTAX AND SEMANTICS INTERFACE ANALYSIS ON VERB TELICITY IN ENGLISH SENTENCE - Ida cahyani (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
As the core of a sentence, a verb can be analysed using syntax and semantic interface based on the verb situation type. One aspect in the verb situation is telicity which shows the process shown by the verb whether involve a bounded activity or unbounded activity with inherent endpoint. This paper analyzes the verbs telicity based on the verb classes proposed by Vendler (1967) namely achievement, accomplishment, activites and states. The aim of the analysis is to find the semantic feature of a verb using syntax and semantics interface. The data in form of sentences were taken from Hemingway’ short story The Short Happy Life of Francis Macomber. The analysis employs descriptive qualitative method using observation technique. The data was presented in both formal and informal method. The results show that ity can be analysed both syntactically and semantically. Accomplishment and achievement verbs are while activities and state verbs are a.